Evaluation of outpatient satisfaction and service quality of Pakistani healthcare projects: Application of a novel synthetic Grey Incidence Analysis model. Issue 4 (8th October 2018) - Javed, Saad Ahmed; Liu, Sifeng
Abstract : Purpose: The purpose of this paper is to analyse the relationship between outpatient satisfaction and the five constructs of healthcare projects' service quality in Pakistan using Deng's grey incidence analysis (GIA) model, absolute degree GIA model (ADGIA), a novel second synthetic degree GIA (SSDGIA) model and two approaches of decision-making under uncertainty. Design/methodology/approach: The study proposes a new synthetic GIA model and demonstrates its feasibility on data ( N =221) collected from both public and private sector healthcare projects of Punjab, the most populous province of Pakistan, using a self-administered questionnaire developed using the original SERVQUAL approach. Findings: The results of decision analysis approach indicated that outpatients' satisfaction from the private sector healthcare projects is higher as compared to the public healthcare projects'. The results from the proposed model revealed that tangibility and reliability play an important role in shaping the patient satisfaction in the public and private sectors, respectively. Originality/value: The study is pioneer in evaluating a healthcare system's service quality using grey system theory. The study proposes the SSDGIA model as a novel method to evaluate parameters comprehensively based on their mutual association (given by absolute degree of grey incidence) and inter-dependencies (given by Deng's degree of grey incidence), and tests the new model in the given scenario. The study is novel in terms of its analysis of data and modelling. The study also proposes a comprehensive structure of the healthcare delivery system of Pakistan.